Perjanjian Sewa Beli Rumah Negara - Prawatya Ido Nurhayati (Widya Yuridika, 2021)
This research is aimed at finding out how far the legal power of the lease and purchase agreement is as a form of agreement that is not regulated in law which is used as a way for a civil servant with a certain position to own a house, which in this case is the country house he has occupied as a house. facilities provided by the state. Based on the rental purchase agreement Number: PER.1129 / Sby / VII / 2002 dated July 30, 2002, with the object of the country house on Jalan Cikampek number 13 Malang City, the author will analyze the validity of the country house rental purchase agreement using the normative juridical method, with based on several legal materials, including Law Number 40 of 1994 concerning State Houses with Government Regulation Number 31 of 2005 concerning Amendments to Government Regulation Number 40 of 1994 concerning State Houses, so that it can be seen whether the state house rental purchase agreement can be the basis for for the National Land Agency to be able to process the transfer of rights to the country house.AbstrakPenelitian Ini ditujukan untuk mengetahui seberapa jauh kekuatan hukum dari perjanjian sewa beli sebagai bentuk perjanjian yang tidak diatur dalam undang-undang yang dipergunakan sebagai jalan bagi seorang Pegawai Negeri Sipil dengan jabatan tertentu untuk memiliki rumah, yang dalam hal ini adalah rumah negara yang telah ditempatinya sebagai fasilitas yang diberikan oleh negara. Didasarkan pada perjanjian sewa beli Nomor : PER.1129/Sby/VII/2002 tanggal 30 Juli 2002, dengan obyek rumah negara di jalan cikampek nomor 13 Kota Malang, maka penulis akan menganalisa keabsahan perjanjian sewa beli rumah negara tersebut dengan metode yuridis normatif, dengan berdasarkan beberapa bahan hukum antara lain Undang-Undang Nomor : 40 Tahun 1994 Tentang Rumah Negara dengan Peraturan Pemerintah Nomor 31 Tahun 2005 Tentang Perubahan Atas Peraturan Pemerintah Nomor 40 Tahun 1994 Tentang Rumah Negara, sehingga dapat diketahui apakah perjanjian sewa beli rumah negara tersebut dapat menjadi dasar bagi Badan Pertanahan Nasional untuk dapat memproses peralihan hak rumah negara tersebut